The Availability of Residential Real Estate Increasing by Means of State Compensation of Prices - Ivanitskiy, Vitaly Viktorovich (Economy of Regions, 2015)
The article analyzes the influence of natural monopolies on the value of residential property, discusses the basic energy resources affecting it. Oil is defined as the main energy resource, its main brands, and their features are considered. The different authors’ perspectives of the impact of oil prices on the real estate prices are considered (“no effect”, “direct effect” and “indirect effect)”. Schemes (models), clearly demonstrating the cause-and-effect relations of the impact of prices of the main energy resources on each other and on the value of residential property, are provided. The stability of relations between the prices of the major energy recourses (between each other as well as between each resource and real estate prices) and residential property prices in the primary market are analyzed. The interval of “crisis” and “crisis-free” time is defined. The impact of the energy in “crisis” and “crisis-free” time is analyzed. The impact of oil prices on the residential property prices is proved through the cement as the main price-determining element in the construction. The introduction of the state target compensation allowing to increase the availability of residential property is proposed as one of the elements of a comprehensive solution of the “housing question”. The size of the state target compensation in absolute (in rubles) and relative (% prices for residential real estate) values is determined, taking into account the sufficient reproduction of the population, and restrictions on the right to use it are introduced. The total value of the state target compensation per total number of homebuyers is calculated, and its share in the expenditures of the consolidated budget and budgets of state extra-budgetary funds is determined. The realization of the state target compensation based on an average annual growth among the major countries of the world is grounded.